Chemical tunnel-splitting-engineering in a dysprosium-based molecular nanomagnet - Sørensen, Mikkel A.; Hansen, Ursula B.; Perfetti, Mauro; Pedersen, Kasper S.; Bartolomé, Elena; Simeoni, Giovanna G.; Mutka, Hannu; Rols, Stéphane; Jeong, Minki; Zivkovic, Ivica; Retuerto, Maria; Arauzo, Ana; et al. (Nature communications, 2018)
Total control over the electronic spin relaxation in molecular nanomagnets is the ultimate goal in the design of new molecules with evermore realizable applications in spin-based devices. For single-ion lanthanide systems, with strong spin–orbit coupling, the potential applications are linked to the energetic structure of the crystal field levels and quantum tunneling within the ground state. Structural engineering of the timescale of these tunneling events via appropriate design of crystal fields represents a fundamental challenge for the synthetic chemist, since tunnel splittings are expected to be suppressed by crystal field environments with sufficiently high-order symmetry. Here, we report the long missing study of the effect of a non-linear ( C 4 ) to pseudo-linear ( D 4d ) change in crystal field symmetry in an otherwise chemically unaltered dysprosium complex. From a purely experimental study of crystal field levels and electronic spin dynamics at milliKelvin temperatures, we demonstrate the ensuing threefold reduction of the tunnel splitting. Suppression of quantum tunneling in molecular magnets is key for their magnetic behaviours to be exploitable. Here, the authors show that tuning the geometry of lanthanide single-ion magnets leads to a suppression of the quantum tunneling, finding a three-fold reduction of the tunnel splitting upon changing the crystal field symmetry.